Connection between the effectiveness of ankylosing spondylitis treatment and the state of bone tissue metabolism - O. V. Syniachenko; Ye. D. Yehudina; M. V. Yermolaeva; O. O. Khaniukov; H. S. Taktashov; Yu. О. Potapov; K. Yu. Gashinova (Zaporožskij Medicinskij Žurnal)
The aim of the study – to evaluate the effectiveness of pathogenetic therapy in patients with ankylosing spondylitis (AS) and the prognostic value of the initial levels of osteoassociated hormones and chemical elements in hair and blood.